Sex‐related differences in cognition with statin usage in a geriatric memory clinic cohort. (31st December 2021) - Chan, Alex K; Lo, Tsz Wai Bentley; Karameh, Wael K; Fornazzari, Luis; Dadone, Gianfranco; Golas, Angela C; Barfett, Joseph; Munoz, David G.; Schweizer, Tom A.; Fischer, Corinne E.
Abstract: Background: Recently, there has been debate for the suitability of statins for geriatric populations and patients with dementia as there is evidence suggesting improved quality of life following discontinuation of therapy in these groups, as well as conflicting evidence surrounding its potential to both prevent and potentiate downstream cognitive deficits. Despite large scale studies being conducted in the past regarding statins and cognition, there is a paucity of literature investigating its interaction with sex, as well as possible associations with other variables such as subjective complaints, neuropsychiatric symptoms, and function. Methods: Analysis was done on patients assessed at a Memory Disorders Clinic at St. Michael's Hospital between 2012 and 2017, comprising a population of 348 patients divided into groups taking daily atorvastatin (N = 45), rosuvastatin (N = 40), and controls (N = 263) (Table 1). Data form the Mini‐Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), Behavioural Neurology Assessment‐Revised (BNA‐R), Neuropsychological Impairment Scale (NIS), The Older Americans Resources and Services (OARS) Activities of Daily Living (ADL) Scale and Neuropsychiatric Inventory Questionnaire (NPI‐Q) were analyzed. Results: Two‐way ANOVA demonstrated a significant interaction between sex, cognitive performance, and statin use in which female statin users scored significantly lower on multiple subdomains of the BNA‐R ( p < 0.05) (Table 2). Patients taking atorvastatin additionally scored lower on CERAD delayed recall, delayed recognition, and in the cumulative recognition domain than other groups ( p < 0.05). Atorvastatin and rosuvastatin were additionally associated with higher frequency of dysphoria and disinhibition, respectively (p < 0.05). No significant results were found in other measures investigated. Conclusions: In addition to minor associations between atorvastatin usage and lower memory performance, findings from this investigation suggest a possible interaction between sex, cognition and statin use that has not been well documented in literature. Though these findings were not reflected in other measures such as subjective complaint or function, further research may be warranted to provide insight into the relationship between sex, statin usage and neurological effects.